ANALISIS KUALITAS KOMUNIKASI ANTARA DOKTER KE PASIEN, KEPERCAYAAN PASIEN PADA DOKTER DAN MUTU PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT GATOEL MOJOKERTO - Prihatini, Renny Padma (Bajang Institute, 2024)
Patient satisfaction is an important indicator of the quality of health services provided by a hospital. The aim of this research is to analyze the influence of the quality of communication between doctors and patients, patient trust in doctors and quality of service on outpatient satisfaction at Gatoel Hospital, Mojokerto. The design of this research is quantitative observational research with a cross sectional approach with the focus of the research directed at analyzing the influence of the quality of communication between doctors and patients, patient trust in doctors and quality of service on outpatient satisfaction at Gatoel Hospital Mojokerto. The total population is 306 respondents and the sample is 100 respondents taken using the Purposive Sampling technique. The findings showed that the majority of respondents had good communication between doctors and patients, namely 54 respondents (54.0%). Almost half of the respondents had good category trust as many as 48 respondents (48.0%). Most of the respondents had sufficient service quality, 56 respondents (56.0%). Most respondents had the satisfaction category of quite satisfied, as many as 53 respondents (53.0%). Based on the results of the Multiple Linear Regression analysis, it shows that with a p-value of 0.000 < 0.05, H1 is accepted so it can be concluded that simultaneously there is an influence on the quality of communication between doctors and patients, patient trust in doctors and quality of service on outpatient satisfaction in hospitals. Gatoel Mojokerto with an influence size of 92.9%. Effective communication between doctors and patients, including listening, clear explanations, and empathy, improves patient understanding and adherence to treatment. Trust in doctors, built through competence, good communication and empathy, as well as reliable, responsive and empathetic service quality, greatly influences patient satisfaction.